Comparison of experimental and numerical studies on the flow structures of hovering hawkmoths. (November 2021) - Liu, Yun; Lozano, Angel David; Hedrick, Tyson L.; Li, Chengyu
Abstract: This study presents an effort on comparing the wake flow structures of hovering insects between experimental visualization and computational simulation. The wake flow on a freely hovering hawkmoth was visualized and captured, utilizing a high-speed schlieren photography system with isopropyl alcohol brushed on the wing surfaces. Meanwhile, an Immersed Boundary Method (IBM) based computational fluid dynamics (CFD) simulation was carried out on a hovering hawkmoth to resolve the entire flow field. On each wing of the hovering hawkmoths, both the schlieren photography experiment and the CFD simulation captured and visualized very alike wake structures, consisting of a vortex loop structure in the down-stroke and tip/root vortices in the up-stroke. Furthermore, the experiment and simulation results are compared by measuring the sizes of the vortex structures. The agreement in flow structure formation and its size between the experiment and simulation suggests that the implemented IBM-based CFD simulation method is capable of simulating the actual flow phenomena on the hovering insect with valid flow structure details such as flow structure size. On the other hand, our study confirms the high-speed schlieren photography's capability of capturing the wake flow structures formation, which is challenging to resolve with other methods.